A study of radioactive contamination of 40Ca100MoO4 crystals for the AMoRE experiment - Lee, J. Y.; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana (IEEE transactions on nuclear science, 2016)
A calcium molybdate (CaMoO4) crystal scintillator, with molybdenum enriched in 100Mo and calcium depleted in 48Ca (40Ca100MoO4), was developed by the Advanced Molybdenum based Rare process Experiment (AMoRE) collaboration to search for a neutrinoless double beta (0νββ) decay of 100Mo. We are planning to use about 10 kg of 40Ca100MoO4 crystals as cryogenic bolometers for the first phase of the experiment (AMoRE-I) at the Yang Yang underground laboratory (Y2L) in Korea. This experiment calls for an extremely low level of radioactive contamination in detectors, particularly by thorium, uranium, and radium decay chains. We measured scintillation properties and radioactive contamination of CaMoO4 and 40Ca100MoO4 crystals at the Y2L. We also estimated the acceptable level of internal radioactive background using Monte Carlo simulation for the AMoRE-I.